Aspects of Voices Appearing in Shin Kyung-Rim’s Poetry - Kim, Bokyoung (International Journal of Korean Humanities and Social Sciences, 2025)
This study explores the transformation in Shin Kyung-rim’s poetic world in the 1970s-1980s by categorizing the vocal modalities that appear in his poems into three analytic categories - the lyric self, the poetic speaker, and the poetic subject. Criticizing the prior studies’ tendency to interpret Shin Kyung-rim’s work under the discursive category of ‘Minjung,’ this study seeks to move beyond ideological frameworks and to reinterpret his poetry through attention to the internal structures of the text and the layers of its practical relationships. When the voice of the lyric self is foregrounded, the poem remains at the level of the poet’s inward confession; by contrast, the emergence of the mudang speaker actively embraces the voice of the other, converting the reader from a mere listener into a performer. Furthermore, the voice of the poetic subject enables readerly intervention, allowing the poem to function as a constantly renewed discourse. These shifts of voice show the process by which the text moves from singularity to complexity and from sameness to otherness, demonstrating that Shin Kyung-rim’s poetry shapes the voice of actual other in reality as living events.